Cathelicidin Modulates Vascular Smooth Muscle Cell Phenotypic Switching through ROS/IL-6 Pathway - Xiaoliang Dong; Di Wu; Yihan Zhang; Lingling Jia; Xiaohua Pan; Jia Sun; Li-Long Pan (MDPI AG, 2020)
Vascular smooth muscle cells (VSMC) are stromal cells of the blood vessels and their differentiation is thought to be essential during atherosclerosis. Cathelicidin-related antimicrobial peptides (CRAMP) are suggested to play a role in the development of atherosclerosis. Even so, the relationship of CRAMP and VSMC remains unclear. The present study was to determine whether CRAMP regulates VSMC phenotypic transformation and underlying mechanisms. We demonstrated that CRAMP could reverse platelet-derived growth factor-BB (PDGF-BB)-induced VSMC phenotypic transformation, evidencing by increasing α-smooth muscle actin (α-SMA), smooth muscle 22α (SM22α) and decreasing of proliferation and migration. Further studies showed that CRAMP inhibited nuclear factor κB (NF-κB)-induced autocrine of interleukin-6 (IL-6), which further activated of janus kinase 2 (JAK2)/signal transducer and activator 3 (STAT3). Meanwhile, our data showed that CRAMP can significantly inhibit PDGF-BB enhanced intracellular reactive oxygen species (ROS) level which further affected the NF-κB signaling pathway, indicating that CRAMP can regulate the phenotypic transformation of VSMC by regulating oxidative stress. These results indicated that CRAMP regulated the differentiation of VSMC by inhibiting ROS-mediated IL-6 autocrine, suggesting that targeting CRAMP is a potential avenue for regulating the differentiation of VSMC and treatment of atherosclerosis.